Translating national net zero policy into local implementation: a UK case study - Nolden, C; Barnes, J; McMillan, E; McDermont, M (European Council for an Energy Efficient Economy, 2024)
In the UK, the decarbonisation of subnational administrative levels such as cities and local authorities more generally can be mainly attributed to national efforts to improve energy efficiency and decarbonise the electricity system. This suggests that place-based transitions to net zero (NZ) are determined largely by the translation of national strategy into local delivery, resourcing, and capabilities combined with the effective balance of power and decision-making capabilities between administrative levels. In this paper we critically interrogate this translation process by comparing and evaluating Climate Action Plans (CAPs) across two English city regions – West of England and West Yorkshire Combined Authorities – which comprise a total of 12 local authorities within. Unlike jurisdictions where local authorities are required to develop energy and climate strategies aligned with national NZ targets, such as The Netherlands, England does not. Overall, our results reveal a misalignment of ambitions, motivations, and resourcing with local and regional NZ delivery being undertaken within a fragmented policy landscape. While UK climate law and resulting strategy collectively determine how supportive environments are for local NZ delivery, a myriad of subnational, regional and local tiers of government with widely diverging responsibilities over people, assets and land have developed their own CAPs with widely diverging NZ targets and ambitions. We find local NZ governance is further hindered by the competitive allocation of funding which favour short-termism over long-term planning horizons necessary to structurally lower energy demand. These findings challenge a top-down framing of NZ policy translation and highlight its detrimental impacts on local decarbonisation efforts and energy efficiency in particular. We conclude with policy recommendations to culture effective and just multi-level governance for NZ delivery.